Copy number variation of a fatty acid desaturase gene Fads2 associated with ecological divergence in freshwater stickleback populations. (25th August 2021) - Ishikawa, Asano; Stuart, Yoel E.; Bolnick, Daniel I.; Kitano, Jun
Abstract : Fitness of aquatic animals can be limited by the scarcity of nutrients such as long-chain polyunsaturated fatty acids, especially docosahexaenoic acid (DHA). DHA availability from diet varies among aquatic habitats, imposing different selective pressures on resident animals to optimize DHA acquisition and synthesis. For example, DHA is generally poor in freshwater ecosystems compared to marine ecosystems. Our previous work revealed that, relative to marine fishes, several freshwater fishes evolved higher copy numbers of the fatty acid desaturase2 ( Fads2 ) gene, which encodes essential enzymes for DHA biosynthesis, likely compensating for the limited availability of DHA in freshwater. Here, we demonstrate that Fads2 copy number also varies between freshwater sticklebacks inhabiting lakes and streams with stream fish having higher Fads2 copy number. Additionally, populations with benthic-like morphology possessed higher Fads2 copy number than those with planktivore-like morphology. This may be because benthic-like fish mainly feed on DHA-deficient prey such as macroinvertebrates whereas planktivore-like fish forage more regularly on DHA-rich prey, like copepods. Our results suggest that Fads2 copy number variation arises from ecological divergence not only between organisms exploiting marine and freshwater habitats but also between freshwater organisms exploiting divergent resources.